Adverse childhood experiences: Adopting a trauma-informed approach to school nursing practice. (2nd March 2019) - White, Sharon
Abstract : In England, there has been a substantial drop in school nursing numbers, from 2915 full time equivalent (FTE) nurses working in school nursing in Sept 2009 (1135 of whom were qualified school nurses) to 2205 (FTE) nurses working in school nursing in November 2018 (1020 of whom were qualified school nurses) (NHS Digital, 2019).